PENDIDIKAN AGAMA ISLAM TERINTEGRASI SEBAGAI PEMBENTUKAN KARAKTER MAHASISWA - Arfah Ibrahim; Fauza Andriyadi (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2022)
This paper will discuss the role of Islamic Religious Education in Higher Education in shaping the character of students. Integrated Islamic Religious Education (PAIT) is one of the most important pillars of character education. Character education will grow well if it starts from the instillation of a religious spirit in children, therefore PAI material in higher education is one of the supports for character education. Through PAI learning, students are taught aqidah as their religious basis, taught the Koran and hadith as a guide for their lives, taught fiqh as legal signs in worship, teaches Islamic history as an example of life, and teaches morals as a guide for human behavior whether in the good or bad category. bad. Therefore, the main goal of PAI learning is the formation of personality in students which is reflected in their behavior and mindset in everyday life. In addition, the success of PAI learning in schools is also determined by the application of appropriate learning methods.